AKUMULASI KADMIUM PADA DAGING IKAN BANDENG ACCUMULATION CADMIUM OF BANDENG FISH FLESH - Prabowo, Rossi (Universitas Wahid Hasyim, 2005)
Analysis Biota irrigate is very importance, because Cd heavy metal characteristic which bioakumulation and biomagnification. Bandeng one of materials consume human being which indirectly with process enchain food and will remove Cd heavy metal accumulation to higher level organism like human being. This Research is executed by using complete random research device. As for its formation consist of 4 group by 3 treatment group that is concentration 80 ppm, 135 ppm, and 180 ppm and also 1 group as control where each by 3 restating times. Cd accumulate analysis conducted in Chemical Laboratory UNNES with AAS technicsly. Research result indicate that biggest accumulation at 180 ppm CdSO4 concentration at third week, this matter because ever greater Cd heavy metal concentration in water test than Cd accumulation in bandeng also will be ever greater, and also longer disclosure time hence Cd accumulation will be progressively growing larger. From research be able biggest Cd accumulation in treatment with concentration 180 ppm at third week equal to 22.32 ppm, the value have exceeded sill maximum limit determined by FDR New Zealand and also FAO that is mentioning sill Cd maximum limit in fish equal to 1 ppm. Cd accumulate factor of bandeng between 0,173 - 16,525. Can be concluded that Cd accumulation in bandeng bared at CdSO4 various concentration will be advance degree in a row improvement CdSO4 concentration in water test, and disclosure time depth. Cd Concentration factor in bandeng mount its rate along the duration disclosure time with CdSO4. Cd Factor Concentration in bandeng the included in low category and range from 0,173 - 16,525. Keywords : Accumulate, Cadmium.